The Study of the Enrofloxacin Adsorption Capability of Cellulose Nanoparticles Conjugated with Aminobenzyl Purin - Hossein Balalzadeh; Seyed Ali Yasini Ardakani; Seyed Hossein Hekmatimoghaddam (Journal of Kerman University of Medical Sciences, 2015)
Background & Aims: Most antibiotics not only inhibit microbial growth, but also can increase the growth of livestock. Although enrofloxacin is one of the most commonly used antibiotics, it has high toxicity on the kidney, liver, and brain. The aim of this study was to synthesize nanocellulose conjugated with aminobenzyl purin and to study its enrofloxacin adsorption capability. Methods: Nanocellulose was first synthesized and conjugated with aminobenzyl purin in the presence of a crosslinker. Then, serial concentrations of conjugated nanocellulose (125, 250, 500, 1000, and 2000 µg/ml) were incubated with enrofloxacin solution of 1000 µg/ml concentration at different temperatures, incubation times, and pH. At the end of incubation, all tubes were centrifuged at the speed of 5000 RPM for 5 minutes and the optical density of the upper layer of solution was obtained using a spectrophotometer with 340 nm wavelength. Finally, the percentage of absorption was calculated. Results: The adsorption tests showed that the variation in concentration of conjugated nanocellulose, and incubation temperature and time did not affect the adsorption, but the variation in pH caused a significant difference in the amount of adsorption. The maximum adsorption was 82.5 % and was observed in acidic conditions for the concentration of 1000 µg/ml. Conclusion: Nanocellulose conjugated with aminobenzyl purin is an efficient adsorbent of enrofluxacin, and could possibly be used in food to adsorb this antibiotic